IBN SINA AND ERICH FROMM: COMPARATIVE ANALYSIS OF THEIR PHILOSOPHICAL IDEAS ON SOCIAL ACTIVITY (Scientific journal of the Fergana State University, 2026)
Comparing the philosophical ideas of Ibn Sina and Erich Fromm on social activism is a very interesting topic, because although these two thinkers belong to different eras, cultures and philosophical traditions, there are certain common points and differences in their views on social activism, human nature and their place in society. While Ibn Sina worked within the peripatetic tradition of medieval Eastern philosophy and the Islamic Enlightenment, Erich Fromm worked within the framework of humanistic psychology and existential philosophy of the 20th century.